Single surgeon coelioscopic orchiectomy of desert tortoises (Gopherus agassizii) for population management. (25th October 2014) - Proença, L. M.; Fowler, S.; Kleine, S.; Quandt, J.; Mullen, C. O.; Divers, S. J.
Abstract : Orchiectomy in chelonians is a challenging procedure, especially in large species with deep and elongated testes and extensive mesorchial attachments. Single surgeon coelioscopic orchiectomy was performed in seven adult desert tortoises ( Gopherus agassizii ), maintained at the Desert Tortoise Conservation Center (DTCC) in Las Vegas, for population management. Surgery was successfully conducted through a bilateral prefemoral approach via sequential vascular clip ligation and radiosurgery (monopolar/bipolar). Bipolar endoscopic forceps were considered indispensable due to the extensive mesorchial attachments and their close association with the kidney. A mechanical arm was effectively used to permit orchiectomy to be completed by a single surgeon. Six of seven animals recovered from anaesthesia. Necropsy demonstrated that the death of the other was unrelated to surgical complications. One animal experienced surgically significant haemorrhage, but still made a clinical recovery. The six tortoises were returned to the DTCC and, six months postoperatively, remain healthy. This small study suggests this minimally invasive technique is an effective method for bilateral orchiectomy in desert tortoises and might be preferable in large chelonians with elongated testes.